2015
DOI: 10.1055/s-0034-1395590
|View full text |Cite
|
Sign up to set email alerts
|

Utility of a Non-Exercise VO2max Prediction Model for Designing Ramp Test Protocols

Abstract: This study investigated the validity of determining the final work rates of cycling and walking ramp-incremented maximal cardiopulmonary exercise tests (CPETs) using a non-exercise model to predict maximal oxygen uptake VO2max and the American College of Sports Medicine ACSM's metabolic equations. The validity of using this methodology to elicit the recommended test duration of between 8 and 12 min was then evaluated. First, 83 subjects visited the laboratory once to perform a cycling (n=49) or walking (n=34) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 27 publications
2
20
0
Order By: Relevance
“…The ramp-incremented maximal CPET was performed as described elsewhere (11). The power output increment was individualized to elicit each participant's limit of tolerance in approximately 10 min.…”
Section: Maximal and Submaximal Exercise Testsmentioning
confidence: 99%
“…The ramp-incremented maximal CPET was performed as described elsewhere (11). The power output increment was individualized to elicit each participant's limit of tolerance in approximately 10 min.…”
Section: Maximal and Submaximal Exercise Testsmentioning
confidence: 99%
“…The WRpeak prediction for the cycle ergometer in this study (mean difference between WRpred and WRpeak was 0·6 W and 95% LoA was −37·6 to 38·8 W) was favourably comparable to the study of Cunha et al . (), which used a different non‐exercise prediction model and the ACSM's metabolic equations to determine the cycle work rate, and found that the mean difference between WRpred and WRpeak was −1 W and 95% LoA was −54·1 to 52·1 W.…”
Section: Discussionmentioning
confidence: 99%
“…Subjects usually need to perform a short maximal test or a warm‐up test to predict the peak work rate before an IET, which is not convenient to implement in daily practice (Myers et al ., ; Arts et al ., ; Loe et al ., ). Recently, there was an attempt to use non‐exercise prediction of maximal normalV˙normalO2 to design IET protocols (Maeder et al ., ; da Silva et al ., ; Cunha et al ., ). For example, a recently published study by Cunha et al .…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations